2021
DOI: 10.3389/fcvm.2021.710425
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL1R1 Coding Variant With Plasma-Level Soluble ST2 and Risk of Aortic Dissection

Abstract: Objective: Aortic dissection (AD) is characterized by an acute onset, rapid progress, and high mortality. Levels of soluble ST2 (sST2) on presentation are elevated in patients with acute AD, which can be used to discriminate AD patients from patients with chest pain. sST2 concentrations were found to be highly heritable in the general population. The aim of this study was to investigate the associations of variations in ST2-related gene expression with sST2 concentrations and AD risk.Methods: This case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Additionally, the upregulation of MYC begins earlier than clinical characteristics [ 22 ]. Interleukin-1 receptor 1 ( IL1R1 ) coding variant was related to TAAD risk through the accumulation of tumorigenicity 2 receptor (ST2) that may induce inflammatory reactions of the aorta and systemic blood vessels, leading to blood vessel damage in the smooth muscle cells (SMCs) [ 23 ]. In our study, IL1R1 and MYC also showed a high diagnostic value and positive correlation with TAAD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the upregulation of MYC begins earlier than clinical characteristics [ 22 ]. Interleukin-1 receptor 1 ( IL1R1 ) coding variant was related to TAAD risk through the accumulation of tumorigenicity 2 receptor (ST2) that may induce inflammatory reactions of the aorta and systemic blood vessels, leading to blood vessel damage in the smooth muscle cells (SMCs) [ 23 ]. In our study, IL1R1 and MYC also showed a high diagnostic value and positive correlation with TAAD.…”
Section: Discussionmentioning
confidence: 99%
“…Serum sST2 is unaffected by potential confounding variables, including age, sex, body mass index, and comorbidities such as renal disease and diabetes ( 41 ), making it a promising biomarker. Relevant clinical investigations have confirmed that serum sST2 can be utilized as an additional parameter for the diagnosis and prognosis of cardiovascular illnesses such as coronary heart disease ( 42 , 43 ), aortic dissection ( 44 , 45 ), and HF ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, biomarkers for screening may offer a solution. For AD assessment, widespread use of the d ‐dimer levels is limited by low specificity, but newer biomarkers such as Aggrecan, IL1R1 and soluble ST2 have shown some potential in pre‐clinical studies 5,6 . Other potential targets include biomarkers from the aortic extracellular matrix such as metalloproteinases, TGF‐β, elastin fragments and those associated with vascular smooth muscle 7 .…”
Section: Competing Interestsmentioning
confidence: 99%
“…For AD assessment, widespread use of the D-dimer levels is limited by low specificity, but newer biomarkers such as Aggrecan, IL1R1 and soluble ST2 have shown some potential in pre-clinical studies. 5,6 Other potential targets include biomarkers from the aortic extracellular matrix such as metalloproteinases, TGF-β, elastin fragments and those associated with vascular smooth muscle. 7 Similarly, micro RNAs (non-coding, small RNA sequences that are stable and detectable in circulating blood) show promise, but all are a long way from demonstrated diagnostic utility in humans.…”
mentioning
confidence: 99%